Стан і тенденції розвитку комбінованого виробництва електричної та теплової енергії в країнах Європейського Союзу - Dubovskoy S.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2004)
The report provides an analysis of statistics on the development of combined heat and power generation technologies in the European Communities countries under the conditions of liberization in the natural gas and electricity markets.